(untitled) (Harmoni, 2013)
Parmalim is the name of a belief or an original religion of tribe Batak in Tomok village, Simanindo subdistrict, Samosir Island, East Sumatera and in Toba Samosir regency, the biggest of Hutatinggi village, Laguboti subdistrict. Headed by Marnangkok Naipospos King, its existence is being into stagnated as the epoch changing. Its followers execute their ritual in Bale Parsakitan every Saturday start from 12 to end headed by Ulu Punguan. Parmalin has spread to 42 region in Indonesia; Medan, East Jakarta, Tangerang, Banten, Riau, Lampung, etc, and its followers has been about 1.161 paterfamilias. The existence of Parmalim was started from the age of Sisingamangaraja XII who created the organization against Dutch. But political aspects oftentimes affect the changes and cause administrative discrimination. The relation between Parmalim and the people around it is well interlaced because in the land Batak, life harmony and tolerance is not determined by religion but tradition of Dalian Natolu.